Needs in Nursing Homes and Their Relation with Cognitive and Functional Decline, Behavioral and Psychological Symptoms - Ferreira, Ana Rita; Dias, Cláudia Camila; Fernandes, Lia (Frontiers in Aging Neuroscience, 2016)
Unmet needs are becoming acknowledged as better predictors of the worst prognostic outcomes than common measures of functional or cognitive decline. Their accurate assessment is a pivotal component of effective care delivery, particularly in institutionalized care where little is known about the needs of its residents, many of whom suffer from dementia and show complex needs. The aims of this study were to describe the needs of an institutionalized sample and to analyze its relationship with demographic and clinical characteristics. A cross-sectional study was conducted with a sample from three nursing homes. All residents were assessed with a comprehensive protocol that included Mini Mental State Examination (MMSE), Geriatric Depression Scale (GDS15), Neuropsychiatric Inventory (NPI) and Adults and Older Adults Functional Inventory (IAFAI). To identify needs, the Camberwell Assessment of Need for the Elderly (CANE) was used. The final sample included 175 residents with a mean age of 80.6(sd=10.1). From these, 58.7% presented cognitive deficit (MMSE) and 45.2% depressive symptoms (GDS). Statistically significant negative correlations were found between MMSE score and met(rs=-0.425), unmet(rs=-0.369) and global needs(rs=-0.565). Data also showed significant correlations between depressive symptoms and unmet(rs=0.683) and global needs(rs=0.407) and between behavioral and psychological symptoms (BPSD) and unmet (rs=0.181) and global needs (rs=0.254). Finally, significant correlations between functional impairment and met(rs=0.642), unmet(rs=0.505) and global needs(rs=0.796) were also found. These results suggest that in this sample, more unmet needs are associated with the worst outcomes measured. This is consistent with previous findings and seems to demonstrate that the needs of those institutionalized elderly remain under-diagnosed and untreated.